Optimalisasi Perawatan Seating & Spindle Exhaust Valve Main Engine pada MV. Lumoso Pratama - Wahyu Kiki Nurhidayat; Mustholiq; Riyadini Utari; Budi Cahyono (Indonesian Journal of Marine Engineering, 2024)
The main engine is engine on board the ship which is the main force drive to move the ship which must be considered for performance and maintenance. The exhaust valve is an engine component that functions as a medium for the exit of exhaust gases from fuel combustion or exhaust gas which is forwarded to the chimney menu or the exhaust gas economizer. As the main component in the main machine, it must maintain performance and carry out maintenance by the rules that have been set. Because the seating exhaust valve and spindle exhaust valve components are always in contact, these two components require more maintenance and attention to support the working process of the main engine. The method used by the author in this study is the qualitative descriptive method. The source of research data obtained by researchers comes from observation, interviews, and documentation and is supported by fishbone and SHEL diagram methods to analyze factors that cause problems in problem formulation. Furthermore, it is analyzed so that it becomes a finding that is given a solution to the problem and becomes a research paper. Factors causing damage to seating and spindle exhaust valves There are various indications found by researchers by the elements of fishbone and SHEL analysis methods, namely poor maintenance factors or PMS, unoriginal spare parts, measurement of guide bushing allowances, cylindrical oil piston rings exceeding running hours, engine room air factors, as well as errors in installation and maintenance efforts carried out on seating and spindle exhaust valves, namely carrying out the appropriate PMS in the manual book, using original spare parts, measurements on guide bushing diameters, check running hours of cylinder oil piston rings, filter installation engine room air and communication between machinists so that there are no errors in the installation of exhaust valve components. Main engine adalah permesinan induk diatas kapal yang menjadi penggerak tenaga utama guna menggerakan kapal yang harus diperhatikan kinerja dan perawatannya. Exhaust valve sebagai komponen mesin yang memiliki fungsi sebagai media keluarnya gas buang sisa pembakaran bahan bakar atau exhaust gas yang diteruskan menu cerobong atau ke exhaust gas economiser. Sebagai komponen utama dalam mesin induk yang harus dijaga performa dan melaksanakan perawatan yang sesuai dengan aturan yang telah ditetapkan. Karena seating exhaust valve dan spindle exhaust valve komponen yang selalu bersentuhan, membuat kedua komponen ini memerlukan perawatan dan perhatian yang lebih agar dapat menunjang proses kerja mesin induk. Metode yang digunakan penulis dalam penelitian ini adalah metode deskriptif kualitatif. Sumber data penelitian yang diperoleh peneliti berasal dari observasi, wawancara, dan dokumentasi serta didukung metode diagram fishbone dan SHEL untuk menganalisis faktor yang menyebabkan masalah pada rumusan masalah. Selanjutnya dianalisa sehingga menjadi sebuah temuan yang diberikan pemecahan masalahnya dan menjadi sebuah tulisan penelitian. Faktor penyebab kerusakan seating dan spindle exhaust valve terdapat berbagai indikasi yang ditemukan peneliti sesuai dengan unsur metode analisis fishbone dan SHEL yaitu faktor pemeliharaan atau PMS yang kurang baik, sparepart yang tidak orisinil, pengukuran kelonggaran guide bushing, ring piston minyak silinder melebihi running hour, faktor udara kamar mesin, serta kesalahan dalam pemasangan dan upaya perawatan yang dilakukan pada seating dan spindle exhaust valve yaitu melaksanakan PMS yang sesuai pada manual book, menggunakan sparepart yang orisinil, pengukuran pada diameter guide bushing, check running hours ring piston minyak silinder, pemasangan filter udara kamar mesin serta komunikasi antar masinis agar tidak terjadi kesalahan dalam pemasangan komponen exhaust valve.